2003
DOI: 10.1007/s00408-003-1033-y
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function Abnormalities Associated with Exposure to Automobile Exhaust in a Diesel Bus Garage and Roads

Abstract: In Kolkata city the road transports are maintained by private and Government organization. A major work force belonged to the State Transport Corporation (KSTC), Government of West-Bengal. The pollution caused by these vehicles affects the workers health and caused different types of respiratory problems. This study was undertaken to assess the pulmonary function status of these workers. City KSTC garage workers were investigated and categorically divided into two group: garage mechanics and the (2) those tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…FEV1) are more sensitive in assessing bronchoconstriction of the airways while PEFR can be an effective measure for home monitoring of lung function. 6 A study done among the weaving workers: assessment of lung function by peak flow meter. Study showed that the mean PEFR of the workers who were suffering from respiratory diseases was 406.75 L/min.…”
Section: Discussionmentioning
confidence: 99%
“…FEV1) are more sensitive in assessing bronchoconstriction of the airways while PEFR can be an effective measure for home monitoring of lung function. 6 A study done among the weaving workers: assessment of lung function by peak flow meter. Study showed that the mean PEFR of the workers who were suffering from respiratory diseases was 406.75 L/min.…”
Section: Discussionmentioning
confidence: 99%
“…Chattopadhyay et al . [2] showed that constant exposure to fumes and gaseous pollutants were associated with reduced forced vital capacity and peak expiratory flow rates, which could cause an alteration of respiratory health. The validity of assessment of PEFR over the other standard PFT (Pulmonary Function Test) indices lies in the context that the other indices (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Automobile exhaust consists of oxides of nitrogen, carbon monoxide, particulate matter, and others, which cause injury to the terminal bronchioles and a decrease in the pulmonary compliance and vital capacity. [3]…”
Section: Introductionmentioning
confidence: 99%